2016
DOI: 10.1007/s11325-016-1370-8
|View full text |Cite
|
Sign up to set email alerts
|

The utility of patient-completed and partner-completed Epworth Sleepiness Scale scores in the evaluation of obstructive sleep apnea

Abstract: Neither patient-completed nor partner-completed ESS scores by themselves have great utility in identifying OSA or predicting its severity. However, taking both scores into consideration together improves the sensitivity and specificity of the screening process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
1
12
0
5
Order By: Relevance
“…The study supports the body of evidences that similarly show that ESS is not a good predictor of the presence of sleep apnea [22,[41][42][43] and less emphasis should be placed on it when determining whether PSG should be performed in patients suspected of having sleep breathing disorder. with screening questionnaires and the Epworth sleepiness scale.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study supports the body of evidences that similarly show that ESS is not a good predictor of the presence of sleep apnea [22,[41][42][43] and less emphasis should be placed on it when determining whether PSG should be performed in patients suspected of having sleep breathing disorder. with screening questionnaires and the Epworth sleepiness scale.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to the risk factors mentioned above, the Epworth sleepiness scale that was developed to subjectively grade the severity of excessive daytime somnolence has been shown by some studies to be predictive of the presence of obstructive sleep apnea [18][19][20]. Some other studies however found it not predictive of obstructed sleep apnea [21][22][23][24]. The Epworth sleepiness scale is a selfadministered questionnaire asking how likely a patient is to doze off while engaging in 8 different activities during daytime and each answer gets a score between 0 and 3 (with the number increasing with severity).…”
Section: Introductionmentioning
confidence: 99%
“…Why then should the ESS fail to correlate with measures of SDB, when SDB is known to cause daytime sleepiness in the general population? A possibility is that ESS is subjective, and patients’ estimation of their own degree of sleepiness can be influenced by factors such as being accustomed to chronic fatigue, disease denial, or employment pressure, particularly for commercial drivers [18, 19]. Another possibility is that patients with ESKD interpret the ESS questions in a manner that mitigates against sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Em vista disso, optou-se por usar um limiar de 10 pontos para classificar os professores como tendo sonolência diurna excessiva, já que esse escore é amplamente utilizado em outros estudos 31 .…”
Section: Discussionunclassified